2013
DOI: 10.3126/aej.v14i0.19787
|View full text |Cite
|
Sign up to set email alerts
|

Screening Wheat Genotypes for Drought Tolerance and Co-relation Study among Morpho-physiological Traits

Abstract: Wheat crop in developing world including

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This study is expected to be helpful in wheat breeding for drought tolerance in Nepal (Poudel et al, 2019). 60 different genotypes including landraces, advanced lines of NWRP, drought check international cultivars, advanced commercial cultivars derived from CIMMYT were experimented in a greenhouse which showed that NPGR 7504 landrace showed drought adaptive traits including high water use efficiency (WUE) and among the Nepalese cultivars Gautam showed the superior drought adaptive traits (Pokhrel et al, 2013). Vijay cultivar of Nepal has been characterized as drought sensitive while Gautam cultivar has been found to show various positive drought related traits in an experiment conducted within a greenhouse comprising of local landraces, advanced commercial CIMMYT derived cultivars and three international check cultivars (Pokharel and Pandey, 2012).…”
Section: Drought Stress Varietal Trails and Breeding In Nepalmentioning
confidence: 99%
“…This study is expected to be helpful in wheat breeding for drought tolerance in Nepal (Poudel et al, 2019). 60 different genotypes including landraces, advanced lines of NWRP, drought check international cultivars, advanced commercial cultivars derived from CIMMYT were experimented in a greenhouse which showed that NPGR 7504 landrace showed drought adaptive traits including high water use efficiency (WUE) and among the Nepalese cultivars Gautam showed the superior drought adaptive traits (Pokhrel et al, 2013). Vijay cultivar of Nepal has been characterized as drought sensitive while Gautam cultivar has been found to show various positive drought related traits in an experiment conducted within a greenhouse comprising of local landraces, advanced commercial CIMMYT derived cultivars and three international check cultivars (Pokharel and Pandey, 2012).…”
Section: Drought Stress Varietal Trails and Breeding In Nepalmentioning
confidence: 99%
“…According to a research conducted by (Ihsan et al, 2016) in four wheat genotypes concluded reduction in height of 54% to 66% and 77% to 88% under mild and severe drought stress respectively. Similarly, according to a genotype screening done by (Pokhrel et al, 2013) a height decrease in 60 genotypes during drought condition ranged from 10% to 53%.…”
Section: Morphological Effect Of Droughtmentioning
confidence: 99%
“…However this number was determined to be 1.71 under stressed condition. Early water deficient condition with heat stress was found to damage the number of tillers which strongly reduced yield (Pokhrel et al, 2013).…”
Section: No Of Effective Plant Populationmentioning
confidence: 99%